Developing framework for using social media in business organizations - Kassem, Gamal; Asfoura, Evan (Edelweiss Applied Science and Technology, 2025)
This study develops a comprehensive framework for integrating social media into business organizations, addressing gaps in existing literature. By conducting an extensive literature review and employing the Technology-Organization-Environment (TOE) framework, the research identifies key factors influencing the adoption of social media across various organizational departments. The proposed framework outlines a step-by-step approach to implement social media effectively, incorporating elements such as planning, platform selection, target audience identification, and relationship building. The methodology includes a Delphi-oriented approach validated by expert interviews, revealing insights into practical applications and highlighting the role of social media in innovation, marketing, recruitment, product development, and sales. The findings emphasize the necessity of a standardized framework to maximize the strategic benefits of social media, offering practical guidance for organizations aiming to enhance their operational efficiency and customer engagement through social platforms.